THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE FINANCIAL PERFORMANCE OF BANKING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Argo Putra Prima (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to analyze the effect of added value. Against ROA (Return on Asset / ROA). Capital Capital Efficiency (SCE) Composition of Return on Assets (ROA). Intellectual capital can be accessed as knowledge, in form, intellectual property and experience that can be used to create wealth. In this study, the population is the entire company located at the Indonesia Stock Exchange (IDX). This study uses the financial statements for the last five years from 2009, 2010, 2011, 2012 and 2013. The results of this study indicate the significance of 0.043 <0 , 05 which can be interpreted Human Resources Efficiency (HCE) significantly to the financial performance (ROA) of limited companies that are in BEI. Thus Ha1 is accepted. Results of Experiment on Human Capital Efficiency (SCE) on Financial Performance (ROA). The significance value of 0.004 <0.05 can be interpreted. SCE efficiency is very significant to financial performance. Thus Ha2 is accepted. The significance value of 0.10> 0.05 can be interpreted. Working Capital Efficiency (CEE) is not significantly significant to the financial performance (ROA) of train companies listed on the BEI. Thus Ha3 is rejected. The results of CEE testing have a negative influence on ROA. The significance value of 0.291> 0.05 which can be interpreted VAIC is not significantly affected the financial performance (ROA) of train companies listed on the BEI. Thus Ha4 is rejected.